2011
DOI: 10.1002/cphc.201100300
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Size Effects on the Spectroscopic and Redox Properties of CdSe Nanocrystals in Solution: The Role of Defect States

Abstract: Two series of CdSe quantum dots (QDs) with different diameters are prepared, according to frequently used protocols of the same synthetic procedure. For each sample the photophysical properties and the potentials for the first reduction and oxidation processes in organic solution are determined. The band gap obtained from electrochemical experiments is compared with that determined from the absorption and luminescence spectra. While the optical band gap decreases upon increasing the nanocrystal diameter, as ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 84 publications
0
38
0
Order By: Relevance
“…This shift was consistent with quantum confinement effects and agreed with literature results published for similar systems. 45 Figure 2a revealed slightly red-shifted absorption bands on going from the aliquot withdrawn at 15 min of synthesis, 482 nm, to the aliquot withdrawn at 180 min of synthesis, 493 nm. This shift suggested that nanoparticle size increased along the synthesis.…”
Section: Cdse Qdsmentioning
confidence: 99%
“…This shift was consistent with quantum confinement effects and agreed with literature results published for similar systems. 45 Figure 2a revealed slightly red-shifted absorption bands on going from the aliquot withdrawn at 15 min of synthesis, 482 nm, to the aliquot withdrawn at 180 min of synthesis, 493 nm. This shift suggested that nanoparticle size increased along the synthesis.…”
Section: Cdse Qdsmentioning
confidence: 99%
“…These techniques have several advantages and disadvantages, but generally speaking it can be said that their use can be laborious, time consuming or requiring expensive instrumentation. Electrochemical techniques have been also used for the characterization of QDs, providing valuable information about the nanocrystals, such as energy bands [8] or surface defects [9]. For instance, cyclic voltammetry has been used to study the quantum confinement and band structure parameters in oleic acid stabilized CdTe dispersions, as a function of nanoparticle size [10].…”
Section: Introductionmentioning
confidence: 99%
“…The band structure and electronic properties can be theoretically calculated with tight-binding (TB) model, effective mass approximation (EMA) and density functional theory (DFT) [4,5], these parameters estimated by experiments under specific conditions vary much from those. Some experimental methods, including photoemission spectroscopy in air (PESA) [6], ultraviolet and X-ray photoelectron spectroscopy (UPS and XPS) [7], scanning tunneling spectroscopy (STS) [8] and cyclic voltammetry (CV) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], exhibit the capability to measure the values of the NC's band structure parameters in special environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still quite complicated for the CV's application to investigate the NC's band structure and electronic properties owing to the following NC's factors: the surface status (including defects [13,14], the ligands [17,21,22] and the dielectric environment), the weak electrochemical redox signals of NCs (especially for the reduction wave), and decomposition upon electrochemical oxidation and reduction. To the best of our knowledge, some groups have examined the influence of the particle size, the surface ligand and particle composition on the band structure and electronic properties of CdSe, CdTe and their alloy (CdSe x Te 1−x ) NCs by the CV and other measurements [11,[15][16][17][18]21] on the band structure and electronic properties of core/shell NCs yielded by the CV method [24].…”
Section: Introductionmentioning
confidence: 99%